Mechanics of Materials - Johnston, Jr E. Russell (MC Graw Hill, 2009)
For the past forty years Beer and Johnston have been the uncontested leaders in the teaching of undergraduate engineering mechanics. Their careful presentation of content, unmatched levels of accuracy, and attention to detail have made their texts the standard for excellence. The revision of their classic "Mechanics of Materials" features an updated art and photo program as well as numerous new and revised homework problems. The text's superior Online Learning Center includes an extensive Self-paced, Mechanics, Algorithmic, Review and Tutorial (S.M.A.R.T.), created by George Staab and Brooks Breeden of The Ohio State University, that provides students with additional help on key concepts. The custom website also features animations for each chapter, lecture powerpoints, and other online resources for both instructors and students.